Investigation Of Silver Oxide Nanoparticles In Polymannose Thin Film On Resistive Switching Characteristics - Au Yong, Huey Leen (Universiti Sains Malaysia, 2022)
Polymannose thin film has shown remarkable properties that are important in resistive switching random-access memory (ReRAM) and multistate switching memory applications. Some of these properties include a high ON/OFF ratio, relatively low READ voltage, high endurance cycle and long retention time. For these reasons, polymannose thin film is said to be a potential bio-organic material in producing the next-generation artificial synapses. However, the resistive switching behaviour of polymannose thin film loaded with metallic nanoparticles has not yet been explored. Therefore, this study aims to examine the effect of different concentrations of silver oxide nanoparticles incorporated in the polymannose thin film. The device can be fabricated with D-mannose powder and ethanol as precursors with different concentrations of silver oxide nanoparticles added which are 0 wt%, 0.5 wt%, 1.0 wt%, 2.0 wt% and 10 wt%. The precursor solutions were drop cast on the film and left dried for 7 hours at 160ºC to form a resistive switching thin film. After the device is successfully fabricated, the read memory window and ON/OFF current ratio of each device were studied in detail. It is found that devices with polymannose loaded with 1 wt% AgO NPs demonstrated the best performance with a read memory window of 0.65 V and a high ON/OFF current ratio of 3.65 x102 at low read voltage (0.5 V). The knowledge gained from this work will be highly beneficial for the future development of the ReRAM.